Enduring evolutionary embellishment of cloudinids in the Cambrian - Park, Tae-Yoon S.; Jung, Jikhan; Lee, Mirinae; Lee, Sangmin; Zhen, Yong Yi; Hua, Hong; Warren, Lucas V. [UNESP]; Hughes, Nigel C. (Royal Soc, 2021)
The Ediacaran-Cambrian transition and the following Cambrian Explosion are among the most fundamental events in the evolutionary history of animals. Understanding these events is enhanced when phylogenetic linkages can be established among animal fossils across this interval and their trait evolution monitored. Doing this is challenging because the fossil record of animal lineages that span this transition is sparse, preserved morphologies generally simple and lifestyles in the Ediacaran and Cambrian commonly quite different. Here, we identify derived characters linking some members of an enigmatic animal group, the cloudinids, which first appeared in the Late Ediacaran, to animals with cnidarian affinity from the Cambrian Series 2 and the Miaolingian. Accordingly, we present the first case of an animal lineage represented in the Ediacaran that endured and diversified successfully throughout the Cambrian Explosion by embellishing its overall robustness and structural complexity. Among other features, dichotomous branching, present in some early cloudinids, compares closely with a cnidarian asexual reproduction mode. Tracking this morphological change from Late Ediacaran to the Miaolingian provides a unique glimpse into how a primeval animal group responded during the Cambrian Explosion.
Keywords: Cloudina; Cambrian Explosion; cnidarians